Upper crust anisotropy of the 2020 Jiashi MS 6.4 earthquake - Li, Jin; Gao, Yuan; Zhou, Shaohui (Frontiers in Earth Science, 2023)
The 2020 Jiashi MS 6.4 earthquake occurred north of the 1997–1998 Jiashi earthquake swarm. To study the upper crustal anisotropy in the source area, we applied microseismic event detection and shear-wave splitting techniques to the seismic data recorded by five stations around the epicenter. First, the earthquake catalog of the Jiashi MS 6.4 earthquake sequence was rebuilt using the “Match & Locate” method. A total of 9,695 earthquake events were obtained, and the number of newly detected earthquakes was approximately 7.3 times the number in the officially released catalog. We analyzed shear-wave splitting according to the updated catalog. The results showed that the dominant polarizations of the fast shear waves were in NW or NNW at the stations BPM, XKR, L6505, and L6513, consistent with the stress near the source area. There are also blind faults with an NNW direction in the strike distributing en echelon and parallel to the main stress direction in the Jiashi seismic area. Thus, the fast shear-wave polarization of the four stations may also reflect the strike of multiple buried NNW faults in the study area. The fast shear-wave polarization of station HLJ, located at the Halajun Basin, was E–W, with the overall trend of the Kalpin thrust nappe structure. However, this station did not show the same NW or NNW fast-wave direction as the four stations previously mentioned. This finding may indicate that the NW-trending buried faults in the Jiashi seismic area have a limited size in both the length and the depth, only reaching northward near the second row of the Kapingtag nappe structure. The temporal trend of the delay time at station HLJ showed that a stress-release process occurred before the MS 6.4 earthquake and that stress-release occurred again after the mainshock. At station XKR, the delay time rapidly increased and then fell in the early period after the MS 6.4 earthquake, indicating that stress accumulated rapidly after the main earthquake but was released during the aftershock sequence. This study provides novel insights into the complex structural characteristics and seismogenic environment in the Jiashi area.